2012
DOI: 10.1074/jbc.m112.376186
|View full text |Cite
|
Sign up to set email alerts
|

Toll/Interleukin-1 Receptor Domain Dimers as the Platform for Activation and Enhanced Inhibition of Toll-like Receptor Signaling

Abstract: Background: TIR domains mediate TLR signaling and are hijacked for immunosuppression by bacteria. Results: Tethering of TIR domains or their dimerization by fusion with coiled-coil segment strongly improved inhibition of TLR signaling. Conclusion:The presence of a coiled-coil segment in bacterial TCPs potentiates inhibition while preventing the constitutive activity of TIR domain dimer. Significance: Dimeric TIR domain represents the platform for the formation of Myddosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
1
32
1
1
Order By: Relevance
“…Tethered MyD88 WT TIR domains exhibit inhibition of TLR signaling at low expression levels but constitutive activity at higher expression levels. 22 We observed the similar dose-dependent response for lymphoma-associated MyD88 TIR-only constructs, namely inhibition of TLR4 signaling upon LPS stimulation at lower expression and increased activation at higher expression levels for the M232T, L265P, and V217F lymphomaassociated mutant ( Figure 1F). Thus, lymphoma-associated TIRdomain mutants display a phenotype similar to that of a forced dimer of WT TIR domains, suggesting that a di/oligomeric MyD88 TIRdomain platform is a prerequisite for the constitutive activation.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Tethered MyD88 WT TIR domains exhibit inhibition of TLR signaling at low expression levels but constitutive activity at higher expression levels. 22 We observed the similar dose-dependent response for lymphoma-associated MyD88 TIR-only constructs, namely inhibition of TLR4 signaling upon LPS stimulation at lower expression and increased activation at higher expression levels for the M232T, L265P, and V217F lymphomaassociated mutant ( Figure 1F). Thus, lymphoma-associated TIRdomain mutants display a phenotype similar to that of a forced dimer of WT TIR domains, suggesting that a di/oligomeric MyD88 TIRdomain platform is a prerequisite for the constitutive activation.…”
supporting
confidence: 49%
“…The isolated MyD88 wild-type (WT) TIR domain has a dominant-negative effect on TLR signaling, 6 but forced TIR domain dimerization, eg, based on the intrinsic affinity of TIR domains of TLR4 21 or tandem constructs of MyD88 TIR domains (tethered TIR domains), constitutively initiate signaling, suggesting that TIR di/oligomerization may initiate nucleation of Myddosomes in the absence of an incoming TLR signaling. 22 Whether and how these results relate to a physiologically relevant process has not been determined so far.…”
Section: Introductionmentioning
confidence: 99%
“…1 B and C), indicating that exchanging one partner in the complex is sufficient to overcome the slower kinetics of CeTIR homodimers. We investigated the specificity of this phenomenon by evaluating the TIR domain from Myd88, which does not induce cell death as a homodimer (4,15,16). Enforced dimerization between HsTIR and the TIR domain from Myd88 did not induce cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enforced homodimerization of the human SARM1 TIR (HsTIR) domain stimulates rapid consumption of NAD + followed by axon degeneration and cell death (4). The capacity of dimerized SARM1 TIR to stimulate NAD + loss and cell death is unique, because dimerization of other human TIR domains does not induce axon degeneration or cell death (4,15,16). Hence, the TIR domain of SARM1 possesses distinct qualities that enable SARM1-dependent NAD + loss after neuronal injury.…”
mentioning
confidence: 99%
“…Furthermore, these studies provided novel insights into the structural interactions and function of TIR domains that could potentially augment the efficacy of TLR agonists and antagonists. Fekonja et al (2012b) showed that the addition of a strong-coiled coil dimerization domain determined the degree of inhibition against various TLRs and prevented activation of the dimeric TIR platform and Piao et al (2013a) identified TRIF sites that are important for interaction with TLR4 and TRAM. Intense interest in the BB loop of TIR domain has guided research efforts in the development of inhibitory peptides (Toshchakov et al, 2007(Toshchakov et al, , 2011Piao et al, 2013a).…”
Section: Novel Approaches For Targeting Toll-like Receptor Signalingmentioning
confidence: 99%